Malaria Parasitemia and Anaemia among Pregnant Women in Umuahia Metropolis - ANC Amadi; PC Nwankwo (Journal of Applied Sciences and Environmental Management)
A study on the prevalence of malaria parasitaemia and anaemia among pregnant women attending Federal Medical Centre (FMC), Umuahia and Nwachinemere Maternity and Child-Care (NMCCD) Ihie in Umuahia metropolis in Abia State Nigeria was carried out between April and October 2010. Blood samples were collected by vein puncture from 500 pregnant women in different trimesters. 300 FMC and 200 from NMCCD. Presence of malaria parasites was observed microscopically on the thin and thick blood smear prepared from each sample. Data were collected and analyzed statistically using chisquare test. A total of 270 (54.0%) pregnant women out of 500 examined were positive for malaria parasites, while 254 (94.1%) were aneamic. FMC had 112 (56.0%) out of the 200 pregnant women examined. There was no significant difference between the results obtained from the two hospitals (P>0.05). Peak prevalence was observed in the first trimester 64.1% while the third trimester showed the lowest 50.7%.Prevalence of malaria was also highest among the primigravidae 56.9% and the multigravidae had the least (50.1%). Anaemia of Hb<11 g/d1 was observed in 254 (94.1%) out of the 270 positive with malaria parasites. Of the 270 infected women, 254 (94.1%) were anaemia. Malaria and anaemia in pregnancy result to low birth weight, induced abortion and eventual death. Reduction and prevention of morbidity and mortality due to malaria and anaemia were discussed.